CCAAT displacement protein/cut homolog recruits G9a histone lysine methyltransferase to repress transcription - Nishio, Hitomi (National Academy of Sciences, 2004)
CCAAT displacement protein/cut homolog (CDP/cut) is a highly conserved homeodomain protein that contains three cut repeat sequences. CDP/cut is a transcriptional factor for many diverse cellular and viral genes that are involved in most cellular processes, including differentiation, development, and proliferation. Here, we report that CDP/cut interacts with a histone lysine methyltransferase (HKMT), G9a, in vivo and in vitro. The deletion of the cut repeats within CDP/cut abrogates the interaction with G9a. The transcriptional repressor function of CDP/cut is mediated through HKMT activity of G9a associated with CDP/cut. We show that the recruitment of G9a to the human p21(waf1/cdi1) promoter is contingent on the interaction with CDP/cut, and CDP/cut is directly associated with an increase in the methylation in vivo of Lys-9 in histone H3 within the CDP/cut-regulatory region of the p21(waf1/cdi1) promoter. The endogenous level of p21(waf1/cdi1) expression is repressed through CDP/cut and mediated by HKMT activity of G9a. Furthermore, we report the identification of G9a as a component of CDP/cut complex. G9a colocalizes with CDP/cut in the nucleus. These results indicate that G9a functions as a transcriptional corepressor in association with a CDP/cut complex. These studies now reveal the interaction of G9a with a sequence-specific transcription factor that regulates gene repression through CDP/cut.